Calculus

posted by .

Find dy/dx by implicit differentiation:
x^2-2xy+y^3 = c

Thank you!

  • Calculus -

    x² - 2xy + y³ = c

    2x - 2y - 2xy' + 3y² y' = 0

    2(x-y) + y'(3y²-2x) = 0

    y' = 2(y-x)/(3y²-2x)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Calculus 1 - implicit differentiation

    I do not understand implicit differentiation. One of the problems are: find y' by implicit differentiation xy+2x+3x^2=4. I would appreciate any help that can be offered.
  2. Calculus 1 - implicit differentiation

    I do not understand implicit differentiation. One of the problems are: find y' by implicit differentiation xy+2x+3x^2=4. I would appreciate any help that can be offered.
  3. Calculus

    Use implicit differentiation to find the second derivative: 2xy^2=4 (nothing is in parenthesis)
  4. Calculus 1 Implicit differentiation

    Help please help me understand what i am doing wrong in this problem! x^3+3x^2y+y^3=8 find dy/dx using implict differentiation. The answer is x^2+2xy -------- but i keep getting x^2y x^2+y^2 ----- x^2+y^2
  5. Calculus

    Use implicit differentiation to find the slope of the tangent line to the curve 2(x^2) + 2xy + 2(y^3)= -18
  6. Calculus

    Find dy/dx by implicit differentiation. x^3 - 3x^2y + 2xy^2 =12 Please show me the work/steps on how to do it.
  7. Calculus

    Implicit differentiation of 5x^2-2xy+7^y
  8. Calculus

    Find dy/dx by implicit differentiation for x^2 - 2xy + y^3 = C
  9. Calculus

    Find dy/dx by implicit differentiation for x^2 - 2xy + y^3 = C
  10. Calculus

    Find y" by implicit differentiation. x^3+y^3 = 1 (x^3)'+(y^3)' = (1)' 3x^2+3y^2(y') = 0 3y^2(y') = -3x^2 y' = -3x^2/3y^2 y' = -x^2/y^2 y" = [(y^2)(-x^2)'-(-x^2)(y^2)']/y^4 y" = [(y^2)(-2x)-(-x^2)(2y)]/y^4 y" = [(-2xy^2)-(-2yx^2)]/y^4 …

More Similar Questions